Advances in portable sensing for urban environments: Understanding cities from a mobility perspective. (July 2021) - Birenboim, Amit; Helbich, Marco; Kwan, Mei-Po
Abstract: Portable sensing, in which lightweight mobile sensors are used to measure stimuli, events, and human behavior, is a new and disruptive data collection paradigm. It has several methodological advantages compared to traditional methods and is suitable for investigating the dynamism of increasingly mobile and urban societies. In this article, we discuss the motivations behind the use of portable sensing and reflect upon the advances, limitations, and future of the field. Although portable sensing is still in its infancy, we foresee that its utilization will grow in the coming years. For portable sensing to become a prevalent and legitimate methodological approach, it is essential to have conceptually strong study designs that are grounded in suitable ethical procedures and comply with data protection regulations. Highlights: The availability and quality of portable sensors is increasing. Portable sensors record high-resolution data continuously and in situ while on the move. Availability and benefits of portable sensors consolidate the "portable sensing paradigm." Portable sensing is likely to become a central research tool.